Dynamic fleet management for international truck transportation focusing on occasional transportation tasks - Schorpp, Steffen; SpringerLink (Online service). (Wiesbaden Gabler, 2011)
Recent developments in IC technologies have facilitated the practical application of dynamic vehicle routing systems. While most of the available dynamic approaches deal with urban area environments, the focus of this thesis is set to wide area dynamic freight transportation covering the entire European continent. Due to its dynamic planning component, the occasional transportation mode - independent of predefined line networks - is considered. The author develops and evaluates two new dynamic planning approaches and incorporates all important real-life restrictions, such as regulations on driving and working hours (EC 561). Numerical tests are carried out with a five-week real-life data set from an international freight forwarder. The results indicate that significant improvements, especially in terms of empty kilometers and service quality, can be achieved.
Literature Review on Dynamic Fleet Management; Development and Evaluation of Two New Dynamic Planning Procedures; Real-Life Case Study at European Freight Forwarding Company
Electronic reproduction.
Keywords: Transportation -- Planning; Business logistics -- Management; Electronic books